Assessing the Effect of Online Learning Platforms in Promoting Inclusive Education for Students with Disabilities - Panggabean, Tongam E; Paramansyah, Arman; Halim, Chandra; Maliha, Siti (PT. BATARI EDU CALYA, 2024)
This study assesses the effectiveness of online learning platforms in promoting inclusive education for students with disabilities. Utilizing a mixed-methods approach, the research combines quantitative data from surveys with qualitative insights from interviews and document analysis. The findings indicate that platforms with comprehensive accessibility features and Universal Design for Learning (UDL) principles significantly enhance educational outcomes and satisfaction for students with disabilities. However, disparities in satisfaction among different disability groups highlight the need for more tailored accommodations. Key themes identified include accessibility, usability, support, engagement, and persistent challenges. The study concludes that while online learning platforms have made significant strides, continuous improvement and stakeholder collaboration are essential for optimizing inclusivity and educational equity.